Developing a strategy and action plan for sustainably digitising specific special collections : a case of Buganda Kingdom collection at the Makerere University Library, Uganda - Van Deventer, Martie (University of Pretoria, 2017)
Mini Dissertation (MIT)--University of Pretoria, 2016.